Implementation of Occupational Safety and Health Management System as an Effort to Prevent Occupational Accidents in the Food Industry - Tia Apriyanti; Tatan Sukwika; Purnomosutji Dyah Prinajati (Journal of Applied Management Research, 2023)
It is essential for companies operating in the industrial sector to implement an occupational safety and health management system (OSHMS). There needs to be control and prevention efforts so that work accidents can be minimized. The success of PT. X in implementing OSHMS as an effort to prevent work accidents. The efforts made by PT. X in overcoming work accidents. Quantitative descriptive research using a purposive sampling method, the sample was selected by 4 people who have in-depth knowledge and competence related to OSH in the company. Data was obtained and analyzed using Risk Management, which refers to the checklist in the PP attachment—50 of 2012. Data analysis is displayed in the form of a percentage number. The research results concluded that the implementation of the occupational safety and health management system in the food industry was achieved with an average score of 80.30% in the excellent category. Efforts made to overcome work accidents include implementing coaching in the form of emergency simulation training and SMK3 education, as well as hazard identification. It is recommended that there be ongoing training to improve the implementation of OSHMS in companies.